2011
DOI: 10.1073/pnas.1110946108
|View full text |Cite
|
Sign up to set email alerts
|

Tripartite motif 8 (TRIM8) modulates TNFα- and IL-1β–triggered NF-κB activation by targeting TAK1 for K63-linked polyubiquitination

Abstract: The tripartite motif (TRIM)-containing proteins are a family of proteins that have been known to be involved in divergent biological processes, including important roles in immune responses through regulating various signaling pathways. In this study, we identified a member of the TRIM family, TRIM8, as a positive regulator of tumor necrosis factor-α (TNFα) and interleukin-1β (IL-1β)-triggered NF-κB activation. Overexpression of TRIM8 activated NF-κB and potentiated TNFα-and IL-1β-induced activation of NF-κB, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
151
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 167 publications
(159 citation statements)
references
References 18 publications
8
151
0
Order By: Relevance
“…TRIM5 inhibits infection of HIV-1 and other retroviruses upon entry into the cell by engaging the viral capsid and inducing premature uncoating [21]. Moreover, it has been reported that interferon signaling and NF-B signaling are regulated by TRIM proteins including TRIM8, TRIM21, TRIM25, TRIM27, TRIM30 and TRIM56 [5,[22][23][24][25][26][27]. Recently, it has been reported that TRIM56 interacts with STING and targets it for lysine 63-linked ubiquitination, followed by induction of STING dimerization and activation of the IFN-promoter [27].…”
Section: Discussionmentioning
confidence: 99%
“…TRIM5 inhibits infection of HIV-1 and other retroviruses upon entry into the cell by engaging the viral capsid and inducing premature uncoating [21]. Moreover, it has been reported that interferon signaling and NF-B signaling are regulated by TRIM proteins including TRIM8, TRIM21, TRIM25, TRIM27, TRIM30 and TRIM56 [5,[22][23][24][25][26][27]. Recently, it has been reported that TRIM56 interacts with STING and targets it for lysine 63-linked ubiquitination, followed by induction of STING dimerization and activation of the IFN-promoter [27].…”
Section: Discussionmentioning
confidence: 99%
“…Additional upstream mechanisms may be controlled by TRIMs detected in our screen, as in the case of TRIM8, which is known to be inducible by IFN-γ (Toniato et al, 2002). TRIM8 activates TAK1 (Li et al, 2011), which is proposed to occur through K63 polyubiquitination. TAK1, in turn, activates AMPK-dependent autophagy (Kanayama et al, 2004;Herrero-Martín et al, 2009;Criollo et al, 2011) by phosphorylating AMPK (Xie et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Constructs-NF-B-and IFN-␤ promoter-luciferase reporter plasmids and mammalian expression plasmids for HAtagged TAK1, TAB1-TAB3, IKK␣/␤/␥, TRAF2, and TRAF6 were described previously (21). Mammalian expression plasmid for FLAG-tagged DUSP14 was constructed by standard molecular biology techniques.…”
Section: Methodsmentioning
confidence: 99%